Disparities in the Use of Guideline-Based Pharmacotherapy Exist for Atherosclerotic Cardiovascular Disease and Heart Failure Patients Who Have Intellectual/Developmental Disabilities in a Commercially Insured Database. Issue 10 (October 2020) - Erickson, Steven R.; Basu, Tanima; Dorsch, Michael P.; Kamdar, Neil
Background: Patients who have intellectual/developmental disabilities (IDDs) develop atherosclerotic cardiovascular disease (ASCVD) or heart failure (HF) at rates similar to or higher than the general population. They also face disparities accessing and using health care services. Objective: To determine if disparities exist in the use of guideline-based pharmacotherapy (GBP) for ASCVD or HF for adults with IDD. Methods: Using the 2014 Clinformatics Data Mart Database, adults with ASCVD or HF were divided into IDD or non-IDD groups. Patients with contraindications for GBP medications were excluded. Use of GBP between IDD and non-IDD groups was examined. Subgroup analysis included comparisons between IDD groups. Results: For HF, 1011 patients with IDD and 236, 638 non-IDD patients were identified. For ASCVD, 2190 IDD and 790, 343 non-IDD patients were identified. We found that 47.9%, 35.8%, and 13.1% of IDD and 58.7%, 48.4%, and 18.9% of non-IDD patients had pharmacy claims for statins ( P < 0.001), β-blockers ( P < 0.001), or antiplatelet therapy ( P < 0.001), respectively. For HF, 46.8% and 50.3% of IDD and 59.8% and 55.4% of non-IDD patients had pharmacy claims for β-blockers (P < 0.001) and angiotensin-converting enzyme (ACE) inhibitors or angiotensin-receptor blockers (ARBs; P = 0.003), respectively. In all but one multivariate regression models patients with IDD were less likely to use GBP than patients in the non-IDD group. Subgroup analysis revealed that patients who had Down syndrome had lower GBP use in 4 of the 5 measures. Conclusion and Relevance: Disparities exist in the use of GBP for patients with IDD with ASCVD or HF. Patients who have an IDD should be examined by clinicians to ensure appropriate access to and use of GBP.